2015
DOI: 10.1073/pnas.1508520112
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative medicine: Current therapies and future directions

Abstract: Organ and tissue loss through disease and injury motivate the development of therapies that can regenerate tissues and decrease reliance on transplantations. Regenerative medicine, an interdisciplinary field that applies engineering and life science principles to promote regeneration, can potentially restore diseased and injured tissues and whole organs. Since the inception of the field several decades ago, a number of regenerative medicine therapies, including those designed for wound healing and orthopedics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
476
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 743 publications
(492 citation statements)
references
References 140 publications
0
476
0
16
Order By: Relevance
“…Finally, the adult liver also harbors regenerative capacity; in mammals, pre-existing multipotent stem cells are found at various anatomical reservoirs such as adipose tissue and bone marrow. Tissue engineering studies of bioscaffolds loaded with immature cell populations have revealed that precursor and stem cells bear the potential of repopulating whole organs (3,4). Moreover, emerging methodologies such as the advent of induced pluripotent cells (iPSC) where a cocktail of transcription factors ( Yamanaka factors ) can be used to reprogram adult cell populations into distinct cell lineages are being intensively pursued.…”
Section: Amphibian and Mammalian Regeneration: The Importance Of Oxygenmentioning
confidence: 99%
“…Finally, the adult liver also harbors regenerative capacity; in mammals, pre-existing multipotent stem cells are found at various anatomical reservoirs such as adipose tissue and bone marrow. Tissue engineering studies of bioscaffolds loaded with immature cell populations have revealed that precursor and stem cells bear the potential of repopulating whole organs (3,4). Moreover, emerging methodologies such as the advent of induced pluripotent cells (iPSC) where a cocktail of transcription factors ( Yamanaka factors ) can be used to reprogram adult cell populations into distinct cell lineages are being intensively pursued.…”
Section: Amphibian and Mammalian Regeneration: The Importance Of Oxygenmentioning
confidence: 99%
“…The appropriate candidates for cell therapy and regenerative medicine are stem cells (1)(2)(3). Three main characteristics of stem cells are high proliferation, self-renewal, and differentiation (4).…”
Section: Introductionmentioning
confidence: 99%
“…In one sense regenerative medicine refers to the highly technical specialty that includes transplantation of cells or biomaterials, tissue precursors (stem cells), or fully formed organs to recover lost structure and function 5. The transplantation of corneas is an example of this sense of regeneration.…”
Section: Cultivating Conditions For Rebuildingmentioning
confidence: 99%